Essential methods of plant sample preparation for light microscopy - Soukup, Aleš; Tylová, Edita (Methods in molecular biology, 2014)
There are various preparatory techniques for light microscopy permitting access to the inner structure of plant body and its development. Minute objects might be processed as whole-mount preparations, while voluminous ones should be separated into smaller pieces. Hereby we summarize some of the "classical" techniques to cut more voluminous objects into slices and access their inner structure either for simple anatomical analysis or for further processing (e.g., histochemistry, immunohistochemistry, in situ hybridization, enzyme histochemistry).
Keywords: imunohistochemie; rostliny; Plants; Immunohistochemistry; Specimen Handling; odběr biologického vzorku; mikroskopie; Microscopy